A self-assembled bioglass hydrogel, preparation method and application thereof

Bioglass spinning fibers are constructed through electrospinning technology and combined with grafted polyphosphate hyaluronic acid and multi-arm polyethylene glycol-polypeptide copolymers to construct a self-assembled bioglass hydrogel, solving the problem that existing materials are difficult to achieve complex functions and achieving efficient 3D cell culture and biocompatibility.

CN116144042BActive Publication Date: 2025-04-18THE FIRST AFFILIATED HOSPITAL OF SOOCHOW UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211674655.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-04-18
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

Existing synthetic biomaterials are difficult to achieve complex functions in materials with chemical composition determination, such as networks that respond to multiple stimuli, suitable for in vitro 3D cell culture and in vivo tissue development.

Method used

Bioglass electrospinning fibers are constructed through electrospinning technology, and blended with grafted polyphosphate hyaluronic acid, combined with multi-arm polyethylene glycol-polypeptide copolymer to quickly construct a self-assembled bioglass hydrogel.

Benefits of technology

The prepared bioglass hydrogel has good mechanical properties and biocompatibility, which can realize in vitro 3D culture of bone marrow mesenchymal stem cells and simulate the composite network of native extracellular matrix in assembly and degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116144042B_ABST
    Figure CN116144042B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a self-assembled bioglass hydrogel. Compared with the prior art, the present invention first uses electrostatic spinning technology to construct bioglass electrospinning fibers, then mixes them with hyaluronic acid grafted with polyphosphoric acid, and then uses positively charged polypeptides to incubate at room temperature to quickly construct a self-assembled bioglass hydrogel. The bioglass hydrogel prepared by the method has good mechanical properties and in vitro and in vivo biocompatibility, and can also achieve in vitro 3D culture of bone marrow mesenchymal stem cells. The gel system prepared by the present invention has a composite network in assembly and degradation, which can better simulate the native extracellular matrix, and provide new tools for mesenchymal stem cells for cell bioengineering, and provide new ideas for the current research on the use of organic-inorganic self-assembled composite materials for cell and tissue engineering, and expand the application prospects of self-assembled hydrogel materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a self-assembled bioglass hydrogel, a preparation method and application thereof. Background Art

[0002] The extracellular matrix (ECM) is a complex network of biomolecules surrounding cells, providing mechanical support and biochemical cues to cells and influencing their morphology, movement and fate. Proteins and glycosaminoglycans are the main components of the extracellular matrix. The extracellular matrix is ​​a viscoelastic material composed mainly of soft polymer networks and hard collagen fibers. Chemically, they are complex and dynamic networks mediated by many different biomacromolecule assembly / degradation reactions. However, animal-derived extracellular matrix materials are not suitable for many biotechnology and biomedical applications. In order to reduce the immunogenicity of animal-derived extracellular matrix materials and minimize batch-to-batch differences, many chemically synthesized hydrogel systems have been developed and customized.

[0003] Most synthetic biomaterials have simple compositions and uniform structures, which can not only mimic the complexity of biochemical signals, but also the intrinsic mechanical and dynamic properties of many natural extracellular matrices. For example, by including non-covalent bonds in the cross-linking chemistry in chemically synthesized biomimetic extracellular matrix materials, stress relaxation (a common rheological feature of many natural tissues) can be adjusted as an independent parameter in synthetic biomaterials. However, since the design of synthetic materials focuses on some biochemical, rheological and dynamic properties, most hydrogels cannot provide the complex functions required for complex cell biological processes, such as in vitro 3D cell culture and in vivo tissue development. Therefore, how to achieve relatively complex functions in materials with defined chemical compositions, such as networks that respond to multiple stimuli, is an important challenge in biomaterial research.

[0004] To develop biomaterials with simple chemical synthesis methods, well-defined chemical compositions, and superior dynamic properties for cell bioengineering, biomimetic extracellular matrix materials constructed using self-assembly techniques represent an ideal model system due to their high biomedical relevance. In vitro expanded mesenchymal stem cells (MSCs) are used clinically to treat a variety of diseases, including stroke, arterial disease, paralysis, and inflammatory diseases such as acute and chronic graft-versus-host disease, autoimmune diseases, and sepsis. However, MSC-based therapies often face difficulties with insufficient cell numbers from patients, low cell survival after injection, and poor retention at the intended disease site. Therefore, researchers have begun to explore different strategies and technologies to improve the utility of MSCs in clinical applications or as a model system for stem cell research. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a self-assembled bioglass hydrogel with high volume porosity and cell permeability, and a preparation method and application thereof.

[0006] The present invention provides a method for preparing a self-assembled bioglass hydrogel, comprising the following steps:

[0007] S1) mixing and incubating the bioglass nanofibers and the hyaluronic acid grafted with polyphosphoric acid in a solvent to obtain a bioglass nanofiber / phosphorylated hyaluronic acid mixed solution;

[0008] S2) mixing and incubating the bioglass nanofiber / phosphorylated hyaluronic acid mixed solution with a multi-arm polyethylene glycol-polypeptide copolymer solution to obtain a self-assembled bioglass hydrogel.

[0009] Preferably, the length of the bioglass nanofiber is 1 to 10 μm;

[0010] The bioglass nanofiber is prepared according to the following method:

[0011] A1) mixing an alkyl silicate, ethanol, water, nitric acid and a calcium source to obtain a sol;

[0012] A2) mixing the sol with a polymer and obtaining fibers after electrospinning;

[0013] A3) The fibers are subjected to heat treatment to obtain bioglass nanofibers.

[0014] Preferably, the mass ratio of the alkyl silicate to the calcium source is (2-5):1;

[0015] The silane alkyl ester is tetraethyl orthosilicate; the calcium source is calcium nitrate;

[0016] The volume ratio of ethanol to water is (10-20):1;

[0017] The concentration of the nitric acid is 0.5-2 mol / L; the volume ratio of the ethanol to the nitric acid is (1-3):1.

[0018] Preferably, the polymer is selected from polyvinyl butyral; the mass ratio of the sol to the polymer is 1:(0.8-1.2);

[0019] The mixing time in step A1) is 15 to 30 hours, and the mixture is allowed to stand for 15 to 30 hours after mixing;

[0020] The mixing time in step A2) is 30 to 60 hours;

[0021] The electrospinning flow rate is 0.5-1 mL / h; the electrospinning voltage is 10-20 kV;

[0022] The temperature of the heating treatment is 400° C. to 800° C.; the time of the heating treatment is 1 to 5 hours.

[0023] Preferably, the grafting rate of the hyaluronic acid grafted with polyphosphoric acid is 10% to 30%;

[0024] The mass ratio of the bioglass nanofiber to the hyaluronic acid grafted with polyphosphoric acid is 1:1 to 1:8.

[0025] Preferably, the hyaluronic acid grafted with polyphosphoric acid is prepared according to the following method:

[0026] The imidazole is reacted with sodium hexametaphosphate in the presence of a carbonyl activating agent to obtain imidazole-modified polyphosphoric acid;

[0027] The imidazole-modified polyphosphoric acid is reacted with aminated hyaluronic acid to obtain hyaluronic acid grafted with polyphosphoric acid.

[0028] Preferably, the amino acid sequence of the polypeptide in the multi-arm polyethylene glycol-polypeptide copolymer is CWGG(KA) x GGRGDSP; x is an integer from 5 to 10.

[0029] Preferably, the mass ratio of the hyaluronic acid grafted with polyphosphoric acid to the multi-arm polyethylene glycol-polypeptide copolymer is 1:1 to 1:5;

[0030] The ratio of solute to solvent in the multi-arm polyethylene glycol-polypeptide copolymer solution is (10-100) mg: 1 mL;

[0031] The volume ratio of the biological glass nanofiber / phosphorylated hyaluronic acid mixed solution to the multi-arm polyethylene glycol-polypeptide copolymer solution is 1:(0.5-2).

[0032] The present invention also provides a self-assembled bioglass hydrogel, comprising a hydrogel composite material and bioglass nanofibers; the hydrogel composite material and the bioglass nanofibers are connected by non-covalent bonds; the hydrogel composite material is formed by a multi-arm polyethylene glycol-polypeptide copolymer and hyaluronic acid grafted with polyphosphoric acid.

[0033] The present invention also provides an application of the self-assembled bioglass hydrogel in 3D cell culture.

[0034] The invention provides a method for preparing a self-assembled bioglass hydrogel, comprising the following steps: S1) mixing and incubating bioglass nanofibers and hyaluronic acid grafted with polyphosphoric acid in a solvent to obtain a bioglass nanofiber / phosphorylated hyaluronic acid mixed solution; S2) mixing and incubating the bioglass nanofiber / phosphorylated hyaluronic acid mixed solution with a multi-arm polyethylene glycol-polypeptide copolymer solution to obtain a self-assembled bioglass hydrogel. Compared with the prior art, the present invention first utilizes electrospinning technology to construct bioglass electrospinning fibers, then mixes them with hyaluronic acid grafted with polyphosphate, and then rapidly constructs a self-assembled bioglass hydrogel by incubating with a positively charged polypeptide at room temperature. The bioglass hydrogel prepared by the method has good mechanical properties and in vitro and in vivo biocompatibility, and can also realize in vitro 3D culture of bone marrow mesenchymal stem cells. The gel system prepared by the present invention has a composite network in assembly and degradation, which can better simulate the native extracellular matrix, and provide a new tool for mesenchymal stem cells to be used in cell bioengineering, and provides a new idea for the current research on the use of organic-inorganic self-assembled composite materials for cell and tissue engineering, and expands the application prospects of self-assembled hydrogel materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A schematic diagram of the preparation process of the self-assembled bioglass hydrogel provided by the present invention;

[0036] Figure 2 A schematic diagram of the preparation process of the self-assembled bioglass hydrogel provided by the present invention;

[0037] Figure 3 This is a microscopic morphology of the self-assembled bioglass hydrogel obtained in Example 1 of the present invention;

[0038] Figure 4 This is a diagram showing the mechanical properties of the self-assembled bioglass hydrogel obtained in Example 1 of the present invention;

[0039] Figure 5 This is a staining image of the culture of mesenchymal stem cells in vitro of the self-assembled bioglass hydrogel obtained in Example 1 of the present invention;

[0040] Figure 6 This is a graph showing the in vivo degradation results of the self-assembled bioglass hydrogel obtained in Example 1 of the present invention;

[0041] Figure 7 This is a pathological section diagram of the in vivo biocompatibility of the self-assembled bioglass hydrogel obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0043] The invention provides a self-assembled bioglass hydrogel, comprising a hydrogel composite material and bioglass nanofibers; the hydrogel composite material and the bioglass nanofibers are connected via non-covalent bonds; the hydrogel composite material is formed by a multi-arm polyethylene glycol-polypeptide copolymer and hyaluronic acid grafted with polyphosphoric acid.

[0044] The present invention innovatively proposes a complex dynamic hydrogel system assembled from a bioactive polypeptide-polyethylene glycol conjugate and polyphosphate-modified hyaluronic acid. The hydrogel with dynamic properties is achieved by combining degradable structural components and reversible dynamic cross-linking, allowing the matrix to effectively adapt to cells and support related cellular functions, ultimately meeting the competing but critical requirements for structural integrity and cells. In addition, the hydrogel composite is non-covalently linked to electrospun bioactive glass nanofibers, introducing physical interfacial bonding between the hydrogel network and the bioglass nanofibers. This composite design enables the material to have higher volume porosity and cell permeability, while achieving a sufficiently high storage modulus required for the composite material to match the mechanical properties of natural tissues.

[0045] The self-assembled bioglass hydrogel provided by the invention comprises a hydrogel composite material and bioglass nanofibers.

[0046] The hydrogel composite material is formed by a multi-arm polyethylene glycol-polypeptide copolymer and hyaluronic acid grafted with polyphosphoric acid; the multi-arm polyethylene glycol-polypeptide copolymer is preferably a four-arm polyethylene glycol-polypeptide copolymer; the amino acid sequence of the polypeptide in the multi-arm polyethylene glycol-polypeptide copolymer is preferably CWGG(KA) x GGRGDSP; x is preferably an integer of 5 to 10, more preferably an integer of 6 to 9, and even more preferably an integer of 6 to 7; in the embodiment provided by the present invention, the amino acid sequence of the polypeptide is specifically CWGGKAKAKAKAKAKAKAKAGGRGDSP; the grafting rate of the hyaluronic acid grafted with polyphosphoric acid is preferably 10% to 30%, more preferably 15% to 25%, even more preferably 18% to 22%, and most preferably 20%; the mass ratio of the hyaluronic acid grafted with polyphosphoric acid to the multi-arm polyethylene glycol-polypeptide copolymer is preferably 1:1 to 1:5, more preferably 1:1 to 1:4, and even more preferably 1:2 to 1:3.

[0047] The hydrogel composite material is connected to the bioglass nanofibers by non-covalent bonds; the length of the bioglass nanofibers is preferably 1 to 10 μm; the diameter of the bioglass nanofibers is preferably 0.5 to 1 mm, more preferably 0.6 to 0.9 mm, and even more preferably 0.8 mm; the main components of the bioglass nanofibers are silicon dioxide and calcium oxide; the mass ratio of the bioglass nanofibers to the hyaluronic acid grafted with polyphosphoric acid is preferably 1:1 to 1:8, more preferably 1:2 to 1:6, even more preferably 1:2 to 1:4, and most preferably 1:3.

[0048] The present invention also provides a method for preparing the above-mentioned self-assembled bioglass hydrogel, comprising the following steps: S1) mixing and incubating bioglass nanofibers and hyaluronic acid grafted with polyphosphoric acid in a solvent to obtain a bioglass nanofiber / phosphorylated hyaluronic acid mixed solution; S2) mixing and incubating the bioglass nanofiber / phosphorylated hyaluronic acid mixed solution with a multi-arm polyethylene glycol-polypeptide copolymer solution to obtain a self-assembled bioglass hydrogel.

[0049] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used; the bioglass nanofibers, hyaluronic acid grafted with polyphosphoric acid, and multi-arm polyethylene glycol-polypeptide copolymer are the same as described above and will not be described in detail here.

[0050] In the present invention, the bioglass nanofiber is prepared according to the following method: A1) mixing alkyl silicate, ethanol, water, nitric acid and a calcium source to obtain a sol; A2) mixing the sol with a polymer, and obtaining fibers after electrospinning; A3) heating the fibers to obtain bioglass nanofibers. Among them, the alkyl silicate is preferably tetraethyl orthosilicate; the calcium source is preferably calcium nitrate; the mass ratio of the alkyl silicate to the calcium source is preferably (2-5):1, more preferably (3-4):1, more preferably (3.5-3.8):1, and most preferably (3.6-3.7):1; the volume ratio of ethanol to water is preferably (10-20):1, more preferably (12-18):1, and more preferably (14-16):1; the concentration of the nitric acid is preferably 0.5-2 mol / L, more preferably 0.8-1.5 mol / L, and more preferably 1-1.2 mol / L; the volume ratio of ethanol to nitric acid is preferably (1-3):1, more preferably (1.5-2.8):1, more preferably (2-2.6):1, and most preferably (2.2-2.5):1; alkyl silicate, ethanol, water, nitric acid and calcium source are mixed; the mixing is preferably carried out at room temperature; the mixing time is preferably 15-30h, more preferably 18-26h, more preferably 20-26h, and most preferably 24h; after mixing, the mixture is preferably allowed to stand for 15-30h, more preferably 18-26h, more preferably 20-26h, and most preferably 24h, to obtain to a sol; mixing the sol with a polymer to obtain a viscosity within the range of electrospinning long continuous fibers; the polymer is preferably polyvinyl butyral (PVB); the mass ratio of the sol to the polymer is preferably 1:(0.8-1.2), more preferably 1:1; the mixing time is preferably 30-60h, more preferably 35-55h, more preferably 40-50h, and most preferably 48h; after mixing, electrospinning is performed to obtain fibers; the electrospinning flow rate is preferably 0.5-1mL / h, more preferably 0.5-0.8mL / h, and more preferably 0.6-0. 7mL / h; the voltage of the electrospinning is preferably 10-20kV, more preferably 12-18kV, more preferably 14-16kV, and most preferably 15kV; the diameter of the fiber is preferably 0.5-1mm, more preferably 0.6-0.9mm, and more preferably 0.8mm; the fiber is heat-treated to obtain bioglass nanofibers; the temperature of the heat treatment is preferably 400℃-800℃, more preferably 500℃-700℃, and more preferably 600℃; the time of the heat treatment is preferably 1-5h, more preferably 2-4h, and more preferably 3h.

[0051] In the present invention, the hyaluronic acid grafted with polyphosphoric acid is prepared according to the following method: imidazole is reacted with sodium hexametaphosphate in the presence of a carbonyl activating agent to obtain imidazole-modified polyphosphoric acid; the imidazole-modified polyphosphoric acid is reacted with aminated hyaluronic acid to obtain hyaluronic acid grafted with polyphosphoric acid. Imidazole is reacted with sodium hexametaphosphate in the presence of a carbonyl activating agent. In the present invention, this step is preferably specifically mixing imidazole and the carbonyl activating agent in water, and then adjusting the pH value to 5.5-6.5, more preferably to 6, adding sodium hexametaphosphate and adjusting the pH value to 5.5-6.5, more preferably to 6, and reacting; the carboxyl activating agent is preferably EDC hydrochloric acid; the molar ratio of imidazole to carboxyl activating agent is preferably (2-4):1, more preferably (2-3.5):1, more preferably (2.5-3):1, and most preferably 2.8:1; in the present invention, In the present invention, hydrochloric acid or sodium hydroxide is preferably used to adjust the pH value of the system; the molar ratio of imidazole to sodium hexametaphosphate is preferably (8-20):1, more preferably (10-15):1, more preferably (13-15):1, and most preferably (13-14):1; the reaction is preferably carried out at room temperature; the reaction time is preferably 0.5-3h, more preferably 1-2.5h, and more preferably 1.5-2h; after the reaction, it is preferably purified by ethanol precipitation, and imidazole-modified polyphosphoric acid can be obtained after freeze-drying; the aminated hyaluronic acid is preferably ethylenediamine hyaluronic acid The aminated hyaluronic acid is preferably obtained by conjugating an amine compound with hyaluronic acid in the presence of a cross-linking agent; the weight average molecular weight of the hyaluronic acid is preferably 50 to 500 kDa, more preferably 80 to 200 kDa, more preferably 80 to 150 kDa, and most preferably 100 kDa; the cross-linking agent is preferably 4-(4,6-dimethoxy-1,3,5-triazine-2-yl)-4-methylmorpholinium chloride (DMTMM); the imidazole-modified polyphosphoric acid is reacted with the aminated hyaluronic acid; the amine group in the aminated hyaluronic acid reacts with the imidazole-modified polyphosphoric acid; The molar ratio of phosphoric acid is preferably (0.1-10):1, more preferably (1-10):1, and more preferably (5-10):1; the pH value of the reaction is preferably 8-9, and more preferably 8.5; the temperature of the reaction is preferably 40°C-60°C, more preferably 45°C-55°C, and more preferably 50°C; the reaction time is preferably 3-8h, more preferably 4-7h, and more preferably 5-6h; after the reaction is completed, the hyaluronic acid grafted with polyphosphoric acid is preferably obtained by dialysis purification with distilled water and freeze-drying; the molecular weight cutoff of the dialysis is preferably 6-8kDa.

[0052] The bioglass nanofibers and the hyaluronic acid grafted with polyphosphoric acid are mixed and incubated in a solvent to obtain a bioglass nanofiber / phosphorylated hyaluronic acid mixed solution; the solvent is any solvent well known to those skilled in the art and is not particularly limited. In the present invention, water is preferred, and ultrapure water is more preferred; the mass ratio of the bioglass nanofibers to the hyaluronic acid grafted with polyphosphoric acid is preferably 1:1 to 1:8, more preferably 1:2 to 1:6, more preferably 1:2 to 1:4, and most preferably 1:3; the hyaluronic acid grafted with polyphosphoric acid and The mass ratio of the solvents is preferably (1-5): (99-95), more preferably (2-4): (98-96), and more preferably (2-3): (98-97); the mixed incubation is preferably carried out at room temperature; the mixed incubation time is preferably 12-24 hours, more preferably 14-20 hours, and more preferably 16-18 hours; after the mixed incubation, the pH value of the system is preferably adjusted to neutral, more preferably 6.8-7.5, and more preferably 7-7.2, to obtain a bioglass nanofiber / phosphorylated hyaluronic acid mixed solution.

[0053] The bioglass nanofiber / phosphorylated hyaluronic acid mixed solution is mixed and incubated with a multi-arm polyethylene glycol-polypeptide copolymer solution to obtain a self-assembled bioglass hydrogel; the solvent of the multi-arm polyethylene glycol-polypeptide copolymer solution is preferably a PBS buffer; the ratio of solute to solvent in the multi-arm polyethylene glycol-polypeptide copolymer solution is preferably (10-100) mg:1 mL, more preferably (30-80) mg:1 mL, more preferably (40-60) mg:1 mL, and most preferably 50 mg:1 mL; the pH value of the multi-arm polyethylene glycol-polypeptide copolymer solution is preferably 6.8-7 .5, more preferably 7-7.2; the mass ratio of the multi-arm polyethylene glycol-polypeptide copolymer to the hyaluronic acid grafted with polyphosphoric acid is preferably 1:1-1:5; the volume ratio of the bioglass nanofiber / phosphorylated hyaluronic acid mixed solution to the multi-arm polyethylene glycol-polypeptide copolymer solution is preferably 1:(0.5-2), more preferably 1:(0.8-1.5), further preferably 1:(0.8-1.2), and most preferably 1:1; the mixed incubation is preferably carried out at room temperature; the mixed incubation time is preferably 5-20 min, more preferably 8-15 min, and further preferably 10 min.

[0054] The present invention firstly utilizes electrostatic spinning technology to construct bioglass electrostatic spinning fibers, then mixes them with hyaluronic acid grafted with polyphosphate, and then rapidly constructs self-assembled bioglass hydrogel by incubating with positively charged polypeptide at room temperature. The bioglass hydrogel prepared by the method has good mechanical properties and in vitro and in vivo biocompatibility, and can realize in vitro 3D culture of bone marrow mesenchymal stem cells. The gel system prepared by the present invention has a composite network in assembly and degradation, which can better simulate the native extracellular matrix, and provide a new tool for mesenchymal stem cells to be used in cell bioengineering, and provides a new idea for the current research on the use of organic-inorganic self-assembled composite materials for cell and tissue engineering, and expands the application prospects of self-assembled hydrogel materials.

[0055] The present invention also provides the use of the self-assembled bioglass hydrogel in 3D cell culture, and further preferably in 3D stem cell culture.

[0056] In order to further illustrate the present invention, a self-assembled bioglass hydrogel, a preparation method and application thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0057] The reagents used in the following examples are all commercially available.

[0058] Example 1

[0059] 1.1 Tetraethyl orthosilicate (TEOS), nitric acid and polyvinyl butyral (PVB) were purchased from Sigma-Aldrich, and calcium nitrate tetrahydrate and ethanol (ethanol) were purchased from VWR. A sol was prepared by mixing 8.2 ml of TEOS, 4.2 ml of ethanol and 0.3 ml of water with 1.9 ml of 1M nitric acid and 2.1 g of calcium nitrate tetrahydrate. The sol was stirred at room temperature for 24 hours and then left to stand for the next 24 hours. PVB was mixed with the sol in equal parts to obtain a viscosity within the range of electrospinning long continuous fibers. The sol was prepared and mixed for 48 hours, and then the sol was electrospun. The sol was electrospun at a flow rate of 0.6 mL / h, and 15 kV was applied to a needle (21 G) 12 cm away from the target (Starter Kit, LinariEngineering SRL) at 24±1°C and a relative humidity of 30-39%. The obtained fiber was heated at 600°C for 3 hours to obtain bioglass electrospun fibers. The main components of spun fibers are silicon dioxide and calcium oxide.

[0060] 1.2 In PBS, ethylenediamine and hyaluronic acid (Mw 100kDa) were conjugated under the action of 4-(4,6-dimethoxy-1,3,5-triazine-2-yl)-4-methylmorpholinium chloride (DMTMM) to synthesize ethylenediamine (EN)-modified HA (HA-EN). Subsequently, polyphosphate-modified HA (HA-PP) was synthesized by combining the imidazole-modified polyphosphoric acid terminal imidazole group with the amine group of HA-EN. The specific scheme is to dissolve 45mM imidazole and 16mM EDC hydrochloric acid in distilled water, and adjust the pH value to 6.0 with 1N hydrochloric acid. Then, sodium hexametaphosphate with a final concentration of 3.3mM was added. After adjusting the pH value to 6.0 with 1N NaOH, the aqueous mixture was kept at room temperature for 1.5h and then purified by ethanol precipitation. The product was freeze-dried for 3 days to obtain imidazole-modified polyphosphoric acid as a white powder. Then, 143mL HA-EN aqueous solution (3.5mg / mL, containing 3.86mM EN group, its disaccharide unit is HA-EN) is mixed with 38.6mM polyphosphoric acid-Im. After adjusting the pH value to 8.5 using 1N NaOH, the solution is reacted at 50°C for 5h, and then purified by dialysis (MWCO=6-8kDa) with distilled water at room temperature. The final product in the form of white powder is obtained by freeze drying for 3 days. Hyaluronic acid grafted with polyphosphoric acid is stored at 4°C. The grafting rate of polyphosphoric acid is 20%.

[0061] 1.3 The synthesis of peptide-starPEG conjugates used in hydrogel assembly was performed by Michael-type addition reaction between maleimide-terminated starPEG and cysteine-terminated peptide (amino acid sequence: CWGGKAKAKAKAKAKAKAGGRGDSP). Both components were dissolved in PBS (pH 7.4) at a total concentration of 80 mg ml -1 The reaction mixture was stirred on a stirring plate for 2 hours. The crude product was analyzed by reverse phase UPLC using a reverse phase C18 analytical column and an isocratic gradient. The crude product was dialyzed in a dialysis tubing with a cutoff of 8 kDa to remove uncoupled peptide and salts. The product was then injected into the UPLC chromatograph again to check the purity. The dialyzed product was lyophilized in water.

[0062] 1.4 Grind 50 mg of the prepared bioglass spinning material in a mortar to prepare bioglass nanofibers with a length of 1 μm to 10 μm.

[0063] 1.5 1 μm to 10 μm bioglass nanofibers were mixed with hyaluronic acid grafted with polyphosphoric acid (concentration 2%) (the mass ratio of bioglass nanofibers to hyaluronic acid grafted with polyphosphoric acid was 1:3) and incubated at room temperature for 16 hours, and then the pH value was adjusted to 7.2.

[0064] 1.6 Dissolve 50 mg of four-arm polyethylene glycol-polypeptide copolymer in 1 ml of PBS and adjust the pH to 7.2.

[0065] 1.7 Mix 250 μL of the bioglass nanofiber / phosphorylated hyaluronic acid mixture with 250 μL of four-arm polyethylene glycol-polypeptide copolymer in a volume ratio of 1:1 (the mass ratio of the multi-arm polyethylene glycol-polypeptide copolymer to the hyaluronic acid grafted with polyphosphoric acid is 2:1), incubate at room temperature for 10 minutes to obtain a self-assembled bioglass hydrogel.

[0066] See also Figure 1 and Figure 2 , Figure 1 and Figure 2 A schematic diagram of the preparation process of the self-assembled bioglass hydrogel provided by the present invention.

[0067] Materials Characterization of Self-Assembled Bioglass Hydrogels:

[0068] The microscopic morphology of the self-assembled bioglass hydrogel was detected by SEM. The specific method is to dehydrate the prepared self-assembled bioglass hydrogel, dry it at the critical point, and then freeze it to make it brittle. The cross section is placed on the stage, and gold is sprayed for 45 seconds using a plasma sputtering instrument. The cross section is then placed under SEM for detection, and the scanning electron microscope image is as follows: Figure 3 shown.

[0069] The mechanical properties of the self-assembled bioglass hydrogel were measured using mechanical testing equipment, and the mechanical properties characterization results were obtained as follows: Figure 4 The specific method is to use a rotational rheometer (shear strain intensity of 10%, frequency of 1 Hz) to monitor the storage modulus and loss modulus of the self-assembled bioglass hydrogel over time.

[0070] In vitro biocompatibility of self-assembled bioglass fiber hydrogels and 3D culture of mesenchymal stem cells: The manufacturers of each culture medium should be given. The ratio of culture medium from different manufacturers may be different.

[0071] Human mesenchymal stem cells were used to stain live and dead cells to determine the effect of the composite scaffold on cell viability at different time points. The specific method was to inoculate the cells in a culture flask and culture them in DMEM / F12 medium (GIBCO, USA) containing 10% fetal bovine serum (GIBCO, USA) and 1% double antibody. When the cells were amplified to the P1 generation, they were digested with 0.25% trypsin, centrifuged at 1500 rpm for 5 min, and the cells were counted. The number of cells was calculated as 1000 / cm 2 The cells were inoculated in 96-well plates. The control group was treated with complete culture medium, and the experimental group was treated with self-assembled bioglass fiber hydrogel + complete culture medium. Each group had 6 wells. Serum-free DMEM / F12 solution containing dead and live cell staining reagent was added and placed at 37°C and 5% CO 2Incubate in the incubator for 10 minutes in the dark. After the incubation, use a laser confocal microscope to take pictures and count the number of live and dead cells. The results are as follows: Figure 5 The results showed that the cell viability in the experimental group was more than 90%, indicating that the self-assembled bioglass fiber hydrogel did not affect cell viability.

[0072] In vivo biocompatibility characterization of self-assembled bioglass fiber hydrogels:

[0073] Subcutaneous injection of self-assembled bioglass fiber hydrogel into mice

[0074] Female immunocompetent hairless SKH1-Elite mice (Charles River, 6-8 weeks old, weighing 24-27 g) were anesthetized with 10% (v / v) desflurane (Baxter) and housed at 27±1°C and 55±5% humidity with a 12-hour light cycle. 50 μL of pre-gelled hydrogel was then injected subcutaneously into the lower back region of each mouse.

[0075] In vivo MRI observation of self-assembled bioglass fiber hydrogel in mice.

[0076] The hydrogel volume and inguinal lymph nodes were analyzed using a dedicated 7T magnetic resonance imaging (MRI) device. A T2-weighted measurement sequence (TRARE) was applied, in which the echo and repetition times were set to 38 ms and 4300 ms, respectively. In addition, a spatial resolution of 150 μm in the xy direction and a slice thickness of 0.8 mm were used for in vivo MRI measurements. The hydrogel volume was quantified using ROVER software. The in vivo degradability results of the self-assembled bioglass hydrogels are shown in Figure 2. Figure 6 shown.

[0077] Immunohistochemical staining of self-assembled bioglass fiber hydrogel

[0078] To study the local reaction of the hydrogel-tissue interface and determine the biocompatibility of the hydrogel, tissue samples were removed 25 days after subcutaneous injection of the hydrogel. Therefore, three SKH-1 mice in each hydrogel group were killed by cervical dislocation, and the remaining hydrogel and surrounding tissue layers were removed surgically. The extracted tissue samples were first cultured in 4% (v / v) PFA for 24h and then cultured in 20% (w / v) sucrose PBS solution at room temperature for 3 days. Before frozen sectioning (5m sectioning, at -30°C), the tissue samples were divided into two and embedded in a PBS solution containing 7.5% (w / v) gelatin and 20% (w / v) sucrose. In order to examine the composition and thickness of the subcutaneous connective tissue layer, hematoxylin-eosin (H&E) overview staining and VanGieson staining were performed according to standard protocols. The thickness of the subcutaneous connective tissue layer of each section was determined by AxioVision software (Carl Zeiss, version 4.8), and length measurements were performed at five points on each side of the remaining hydrogel (pointing toward the skin or muscle site). Figure 7 shown.

[0079] Based on the above results, it can be seen that: (1) the self-assembled bioglass fiber hydrogel obtained by the present invention has good mechanical properties; (2) the self-assembled bioglass fiber hydrogel obtained by the present invention has stable in vitro biocompatibility; (3) the self-assembled bioglass fiber hydrogel obtained by the present invention has stable biocompatibility; 4) the self-assembled bioglass fiber hydrogel obtained by the present invention has good support for the 3D culture of mesenchymal stem cells.

[0080] In summary, the present invention innovatively proposes a method for preparing a self-assembled bioglass hydrogel and applies it to the field of stem cell 3D culture. The self-assembled bioglass hydrogel prepared by this method has good mechanical properties and in vitro and in vivo biocompatibility, and can also achieve in vitro 3D culture of bone marrow mesenchymal stem cells. The present invention provides a new idea for the current research on the use of organic-inorganic self-assembled composite materials for cell and tissue engineering, and expands the application prospects of self-assembled hydrogel materials.

Claims

1. A method for preparing a self-assembled bioglass hydrogel, characterized in that: The following steps are involved: S1) mixing and incubating the bioglass nanofibers and the hyaluronic acid grafted with polyphosphoric acid in a solvent to obtain a bioglass nanofiber / phosphorylated hyaluronic acid mixed solution; S2) mixing and incubating the bioglass nanofiber / phosphorylated hyaluronic acid mixed solution with a multi-arm polyethylene glycol-polypeptide copolymer solution to obtain a self-assembled bioglass hydrogel; The bioglass nanofiber is prepared according to the following method: A1) mixing an alkyl silicate, ethanol, water, nitric acid and a calcium source to obtain a sol; A2) mixing the sol with a polymer and obtaining fibers through electrospinning; A3) heating the fibers to obtain bioglass nanofibers; The hyaluronic acid grafted with polyphosphoric acid is prepared according to the following method: The imidazole is reacted with sodium hexametaphosphate in the presence of a carbonyl activating agent to obtain imidazole-modified polyphosphoric acid; reacting the imidazole-modified polyphosphoric acid with aminated hyaluronic acid to obtain hyaluronic acid grafted with polyphosphoric acid; The amino acid sequence of the polypeptide in the multi-arm polyethylene glycol-polypeptide copolymer is CWGG (KA) x GGRGDSP; x is an integer from 5 to 10; The mass ratio of the bioglass nanofibers to the hyaluronic acid grafted with polyphosphoric acid is 1:1 to 1:8; The mass ratio of the hyaluronic acid grafted with polyphosphoric acid to the multi-arm polyethylene glycol-polypeptide copolymer is 1:1 to 1:5; The mass ratio of the alkyl silicate to the calcium source is (2-5):1; The polymer is selected from polyvinyl butyral; the mass ratio of the sol to the polymer is 1:(0.8-1.2).

2. The preparation method according to claim 1, characterized in that: The length of the bioglass nanofiber is 1-10 μm.

3. The preparation method according to claim 1, characterized in that: The alkyl silicate is tetraethyl orthosilicate; the calcium source is calcium nitrate; The volume ratio of ethanol to water is (10-20):1; The concentration of the nitric acid is 0.5-2 mol / L; the volume ratio of the ethanol to the nitric acid is (1-3):

1.

4. The preparation method according to claim 1, characterized in that: The mixing time in step A1) is 15 to 30 hours, and the mixture is allowed to stand for 15 to 30 hours after mixing; The mixing time in step A2) is 30 to 60 hours; The electrospinning flow rate is 0.5-1 mL / h; the electrospinning voltage is 10-20 kV; The temperature of the heating treatment is 400° C. to 800° C.; the time of the heating treatment is 1 to 5 h.

5. The preparation method according to claim 1, characterized in that: The grafting rate of the hyaluronic acid grafted with polyphosphoric acid is 10% to 30%.

6. The preparation method according to claim 1, characterized in that: The ratio of solute to solvent in the multi-arm polyethylene glycol-polypeptide copolymer solution is (10-100) mg: 1 mL; The volume ratio of the bioglass nanofiber / phosphorylated hyaluronic acid mixed solution to the multi-arm polyethylene glycol-polypeptide copolymer solution is 1: (0.5-2).

7. A self-assembled bioglass hydrogel prepared by the preparation method of claim 1, characterized in that: The invention comprises a hydrogel composite material and biological glass nanofibers; the hydrogel composite material and the biological glass nanofibers are connected via non-covalent bonds; the hydrogel composite material is formed by a multi-arm polyethylene glycol-polypeptide copolymer and hyaluronic acid grafted with polyphosphoric acid.

8. Use of the self-assembled bioglass hydrogel prepared by any one of the preparation methods of claims 1 to 6 or the self-assembled bioglass hydrogel according to claim 7 in 3D cell culture; the use is for purposes other than disease diagnosis and treatment.